Fabrication of organic bulk heterojunction solar cells screenprinting - Mercado, Candy C. (Philippine Engineering Journal)
An organic solar cell composed of Poly (2-methoxy-5-(2-methoxy-5-(2'-ethyl-hexyloxy)-1,4-phenylene vinylene)(MEH-PPV) and (6,6)-phenyl C61-butyric acid methyl ester (PCBM) was fabricated by screenprinting. This study is part of a research to drive the cost of PV production down and enable widespread use of the sun's energy. MEH-PPV, a conjugated polymer, becomes semiconducting upon photodoping and when in contact with PCBM, a fullerene derivative, a continuous photocurrent is obtained. Screenprinting was possible because of the ability of both MEH-PPV and PCBM to be processed from a solution of Chlorobenzene. Screenprinting experiments showed that solution has very thin viscosity and requires very high print speeds, 300 to 600 mm/s or more, for best film uniformity. Screenprinting process was also successfully applied to ITO etching and on glass substrates opening the way to the possibility of a fully screenprinted organic solar cell.